The Metabolic Score for Insulin Resistance Index is Superior to the Triglyceride and Glucose Index in Identifying Nonalcoholic Fatty Liver Disease in Hyperuricemia Subjects - Shu Y; Huang G; Mao Y (Diabetes, Metabolic Syndrome and Obesity, 2023)
Yimeng Shu,1,2 Guoqing Huang,1,2 Yushan Mao1 1Department of Endocrinology, The First Affiliated Hospital of Ningbo University, Ningbo, People’s Republic of China; 2Health Science Center, Ningbo University, Ningbo, People’s Republic of ChinaCorrespondence: Guoqing Huang; Yushan Mao, Department of Endocrinology, The First Affiliated Hospital of Ningbo University, 247 Renmin Road, Ningbo, People’s Republic of China, Tel +86 15737939838 ; +86 13867878937, Email guoqinghuang1992@163.com; maoyushan@nbu.edu.cnPurpose: Hyperuricemia (HUA) is a recognized risk factor for non-alcoholic fatty liver disease (NAFLD). Early diagnosis and the identification of predictive factors are important for the HUA population. This study aimed to investigate the potential relationship between the metabolic score for insulin resistance (METS-IR) index and the triglyceride and glucose (TyG) index with NAFLD in individuals with HUA.Patients and Methods: A total of 5537 HUA participants were included in the study. Hepatic ultrasonography was conducted following the latest diagnostic criteria to diagnose NAFLD. The relationship between the TyG and METS-IR index and NAFLD was evaluated by multivariable logistic regression analysis and restricted cubic spline model (RCS). In addition, the area under the curve (AUC), positive likelihood ratio, and negative likelihood ratio were explored to compare the predictive value of IR surrogates for NAFLD with HUA. The AUCs of the two indicators were compared using the DeLong test.Results: Multivariable logistic regression analysis revealed that elevated TyG (OR = 2.285, 95% CI: 1.525, 3.428) and METS-IR (OR = 1.242, 95% CI: 1.219, 1.266) indices significantly increase the risk of NAFLD. Meanwhile, the RCS analysis revealed a -log-shaped nonlinear relationship between NAFLD risk and the METS-IR index (P non-linear < 0.001), contrasting with the linear association observed with the TyG index (P non-linear = 0.763). Notably, the risk of NAFLD demonstrated a significant escalation when the METS-IR index exceeded the threshold of 39.208 (OR=1). Compared to the TyG index (AUC = 0.734, 95% CI: 0.721~0.748), the METS-IR index (AUC = 0.821, 95% CI: 0.810~0.832) demonstrated superior predictive value for NAFLD in individuals with HUA according to the DeLong test.Conclusion: In the HUA population, the METS-IR index has a higher predictive value for NAFLD than the TyG index, contributing to early diagnosis and disease prevention.Keywords: non-alcoholic fatty liver disease, hyperuricemia, the triglyceride and glucose index, the metabolic score for insulin resistance index, inflammation